Second International Handbook of Educational Change
XXVII, 1077 p.
Keywords: The two volumes of the second edition of the International Handbook of Educational Change comprise a totally new, and updated collection of the most critical and cutting-edge ideas in educational change. Written by the most influential thinkers in the field, these volumes cover educational change at both the theoretical and practical levels. The updated handbook remains connected to the classical concerns of the field, such as educational innovation, reform, and change management, and also offers new insights into educational change that have been brought about by social change and shifting contexts of educational reform. Like the first best selling Handbook, this one will also undoubtedly become an essential resource for people involved in all spheres of education, from classroom teachers, teacher leaders and administrators to educational researchers, curriculum developers, and university professors. No other work provides such a wide-ranging and comprehensive examination of the field of educational change.